2021
DOI: 10.1021/acsomega.1c03160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Concentration on the Oxidative Thermodynamics and Spontaneous Combustion of Pulverized Coal

Abstract: Spontaneous combustion of pulverized coal has become a safety topic and has been extensively researched. This study using differential scanning calorimetry investigated the exothermic characteristics and spontaneous combustion risk of three metamorphic pulverized coal samples during oxidative combustion, for oxygen concentrations of 21, 19, 17, 15, 13, 11, 9, 7, and 5 vol %. Results indicated that decreased oxygen concentrations reduced exothermic intensity and substantially increased ignition temperatures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…With untreated biomass having a volatile matter content of 60.52%, the sample is highly likely to be more reactive and easily combustible. As seen from Table , biomass also possesses high oxygen concentration which leads to an increase in the self-ignition attribute of fuels and their SPONCOM liability according to Huangfu et al and Ren et al Furthermore, it can be also seen from Table that biomass is low-quality fuel, given that it had a low calorific value of 17.28 MJ/kg.…”
Section: Resultsmentioning
confidence: 95%
“…With untreated biomass having a volatile matter content of 60.52%, the sample is highly likely to be more reactive and easily combustible. As seen from Table , biomass also possesses high oxygen concentration which leads to an increase in the self-ignition attribute of fuels and their SPONCOM liability according to Huangfu et al and Ren et al Furthermore, it can be also seen from Table that biomass is low-quality fuel, given that it had a low calorific value of 17.28 MJ/kg.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, experiments studied the effects of various parameters, such as coal type, particle size, heating rate, ambient temperature, and gas composition for the single coal particle flames. In particular, Ren predicted the effect of oxygen content on spontaneous pulverized coal combustion, and the results indicated that the ignition temperature substantially increases with the decrease of oxygen concentration and exothermic intensity. Saha , studied the effect of the oxygen concentration and turbulence state on the combustion characteristics of pulverized brown coal with moderate or intense low oxygen dilution (MILD) combustion conditions using experimental and numerical simulation methods.…”
Section: Introductionmentioning
confidence: 99%